ASSESSMENT OF NOMINAL SHEAR STRENGTH OF REINFORCED CONCRETE COLUMN - Dea Fauziah Larasati; Harun Alrasyid; Data Iranata (Institut Teknologi Sepuluh Nopember, 2021)
: SNI 2847-2019 and ACI 318-19 have regulated the use of materials in the design for shear strength. This study presents an evaluation of nominal shear strength in Reinforced Concrete (RC) column from SNI 2847-2019 and ACI 318-19 by variants of the RC columns experimental database. RC column variants consist of normal strength and high strength RC column with a total of 162 specimens. Furthermore, the database also provides a variety of shear span to depth ratio and axial-load ratio. In this study, the calculation was carried out the mean and the coefficient of variation of measured to calculated strength ratio which is according to SNI, ACI, and other experimental models. Both SNI 2847-2019 and ACI 318-19 have 2 different (concrete nominal shear strength) equations. The calculation results show that the equation is more conservative in both SNI and ACI compared to other nominal shear strength equations. Overall, the combination of both normal strength and high strength RC columns, the calculation using ACI 318-19 with the first nominal shear strength equation can be said to be more conservative than any other calculations models. This study also shows that by using the ACI 318-19 model in the second equation which is used the size effect modification factor , the results do not have a significant effect because the value is close to 1.